Putative RopGAPs impact division plane selection and interact with kinesin-12 POK1 - Stoeckle, Dorothee; Herrmann, Arvid; Lipka, Elisabeth; Lauster, Theresa; Gavidia, Richard; Zimmermann, Steffi; Müller, Sabine (Nature Plants, 2016)
Cell shape is defined by the surrounding cell walls in plants. Thus, spatial control over cell division planes and cell expansion polarity are essential to maintain cell morphology. In eukaryotes, cell polarity and expansion are controlled by Rho GTPase signalling, regulating cytoskeletal reorganization and vesicle trafficking1. However, until now, Rho signalling was not implicated in mitotic events in plants. Here, we report a pair of putative Rho GTPase activating proteins (RhoGAPs) that interact with the mitosis-specific kinesin-12 POK1, a core component of the cortical division zone/site (CDZ/CDS) that is required for division plane maintenance in Arabidopsis 2-4. The designated pleckstrin homology GAPs (PHGAPs) are cytoplasmic and plasma membrane associated in interphase, but during mitosis they additionally localize to the CDZ/CDS in a POK-dependent manner. In contrast to pok1 pok2 mutants, phgap1 phgap2 double mutants show moderate cell wall positioning defects as a consequence of inaccurate positioning of the cortical division zone marker POK1. We conclude that loss of PHGAP function interferes with division plane selection in proliferative cell divisions.
CRIS-Team Scopus Importer:2021-07-01